Clinical Characteristics and Outcomes of Coronavirus Disease 2019 (COVID-19) in Pregnant Women: A Propensity Score–Matched Analysis of Data From the COVID-19 Registry Japan. (17th January 2022) - Shoji, Kensuke; Tsuzuki, Shinya; Akiyama, Takayuki; Matsunaga, Nobuaki; Asai, Yusuke; Suzuki, Setsuko; Iwamoto, Noriko; Funaki, Takanori; Yamada, Masaki; Ozawa, Nobuaki; Yamaguchi, Koushi; Miyairi, Isao; et al.
Abstract: Background: Several studies have investigated whether pregnancy is a risk factor for developing severe coronavirus disease 2019 (COVID-19); however, the results remain controversial. In addition, the information regarding risk factors for developing severe COVID-19 in pregnant women is limited. Methods: A retrospective cohort study analyzing the data from the nationwide COVID-19 registry in Japan was conducted. Propensity score–matched analysis was performed to compare COVID-19 severity between pregnant and nonpregnant women. Multivariate analysis was also conducted to evaluate risk factors for developing moderate-to-severe COVID-19 in pregnant women. Results: During the study period, 254 pregnant and 3752 nonpregnant women of reproductive age were identified. After propensity score matching, 187 pregnant women and 935 nonpregnant women were selected. A composite outcome of moderate-to-severe COVID-19 was more frequently observed in pregnant women than that of nonpregnant women (n = 18 [9.6%] vs n = 46 [4.9%]; P = .0155). In multivariate analysis, the presence of underlying diseases and being in the second-to-third trimester of pregnancy were recognized as risk factors for moderate-to-severe COVID-19 in pregnant women (odds ratio [95% confidence interval]: 5.295 [1.21–23.069] and 3.871 [1.201–12.477], respectively). Conclusions: Pregnancy could be a risk factor for moderate-to-severe COVID-19 for women in Japan. In addition to the presence of comorbidities, advanced pregnancy stages may contribute to greater risks for developing moderate-to-severe COVID-19 in pregnant women. Abstract : Propensity score–matched analysis showed that pregnancy could be a risk factor for moderate-to-severe COVID-19 in Japan. In addition to presence of comorbidities, later gestational age may be associated with severity of COVID-19 in pregnant women.